Is Percutaneous Vertebroplasty without Pretreatment Venography Safe? Evaluation of 205 Consecutives Procedures - Vasconcelos, Cristiana; Gailloud, Philippe; Beauchamp, Norman J.; Heck, Donald V.; Murphy, Kieran J. (American Journal of Neuroradiology, 2002)
BACKGROUND AND PURPOSE: Vertebral venography has been advocated before bone cement injection when performing percutaneous vertebroplasty (PV) for benign or malignant lesions of the spine. Although venography can document sites of potential leakage during subsequent cement application, stagnant contrast agent renders the cement injection more difficult to monitor, and an allergic reaction to contrast agent remains a potential risk. We evaluated our experience with PV without prior venographic evaluation.METHODS: Two hundred five consecutive PV procedures performed in 137 patients without pretreatment venography were evaluated for complications linked to bone cement injection. Treated lesions were 172 benign compression fractures, 27 metastases, two hemangiomas, and four multiple myelomas. PV was performed with a single-pedicle technique in 146 cases and a two-pedicle technique in 59 cases.RESULTS: No major complication occurred in our series. Three minor complications (1.5%) were documented: One patient had a transient episode of arterial hypotension during cement injection, without cement leak; one patient had a spontaneously resolving patch of cutaneous hypoesthesia at the puncture site; and one patient had a radiculopathy four levels above the treated level, not caused by cement deposition, and successfully treated with a nerve block. None of these three minor complications were related to cement leakage.CONCLUSION: PV can, in our experience, be performed safely without prior angiographic evaluation of the vertebral venous system.